Synthesis, Characterization, and Evaluation of Antimicrobial Activities of Chitosan and Carboxymethyl Chitosan Schiff-Base/Silver Nanoparticles. (15th March 2017) - Khalil, Ahmed M.; Abdel-Monem, Reham A.; Darwesh, Osama M.; Hashim, Ahmed I.; Nada, Afaf A.; Rabie, Samira T.
Abstract : Schiff-bases of chitosan (CS) and carboxymethyl chitosan (CMCS)/silver nanoparticles (AgNPs) have been synthesized, characterized, and evaluated as antimicrobial agents against two Gram +ve bacteria ( Bacillus cereus and Staphylococcus aureus ) and two Gram −ve bacteria ( Escherichia coli and Pseudomonas aeruginosa ) in addition to Candida albicans as a fungus. The in situ reactions of CS and/or CMCS with some pyrazole aldehyde derivatives in acidic media containing silver nitrate to yield silver nanoparticles loaded onto CS and CMCS/Schiff-bases were carried out. Characterizations of the prepared compounds via FTIR spectroscopy, SEM, TEM, and TGA were carried out. Schiff-bases/silver nanoparticles of CS and CMCS showed higher antimicrobial activity than the blank CS and CMCS. The presence of AgNO3 (3% wt%) displayed high antibacterial efficiencies with inhibition zones in the extent of 19–39 mm. TEM analysis showed that the size of the silver nanoparticles is in the range of 4–28 nm for the prepared nanocomposites.